2016
DOI: 10.4103/0019-5278.183833
|View full text |Cite
|
Sign up to set email alerts
|

Comparative cross-sectional study for understanding the burden of low back pain among public bus transport drivers

Abstract: Background:Even though low back pain (LBP) is common, some occupations pose a higher risk. Identifying these occupations and specific factors will help to reduce the suffering and burden. This study aims to compare the prevalence of chronic LBP among bus drivers and to find its association with some occupational factors.Materials and Methods:It is a cross-sectional study to compare prevalence of LBP and factors associated with it, in two groups of drivers (n = 178) and nondrivers (n = 184).Results:The 10 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 30 publications
3
20
1
Order By: Relevance
“…This finding is higher than what was reported in many studies in Africa, for example, Akinpelu et al [14] in Nigeria reported a prevalence of 64.8% whereas Abledu et al [15] in Ghana reported a figure of 58.8%. Our figure is also higher than what was reported in Asia, for example, Tamrin et al [16] reported a prevalence of 60.4% in Malaysia, whereas Jadhav [17] in India reported 67.4% prevalence of LBP among public bus drivers. Even on comparison with many studies in developed countries [4,18] , our figure was relatively higher.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…This finding is higher than what was reported in many studies in Africa, for example, Akinpelu et al [14] in Nigeria reported a prevalence of 64.8% whereas Abledu et al [15] in Ghana reported a figure of 58.8%. Our figure is also higher than what was reported in Asia, for example, Tamrin et al [16] reported a prevalence of 60.4% in Malaysia, whereas Jadhav [17] in India reported 67.4% prevalence of LBP among public bus drivers. Even on comparison with many studies in developed countries [4,18] , our figure was relatively higher.…”
Section: Discussioncontrasting
confidence: 69%
“…The current study findings showed insignificant association between work satisfaction and LBP. The literatures showed inconsistent results regarding this association as some were in accordance with our finding [15,17] whereas other studies were in contrary to ours [10,24] .…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Meanwhile, 13% of the participants reported a maximum of 6 days of LBP-related absenteeism in the second half of the year, 2% of the workers reported 7-14 days, 3% reported 15-30 days, and 2% reported more than 31 days of absenteeism [18]. As LBP is more prevalent in some occupations, identifying these occupations can help to minimize the occurrence and the outcomes of LBP [19]. In a study conducted on Greek shipyard workers, LBP-related absenteeism was reported in relation to the factors such as age, height, BMI, and smoking.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted among taxi drivers in Nigeria, more than half ( 67%) of drivers reported discomfort in the neck, about 18% & 20% reported symptoms in right & left wrist joints respectively [11]. Jadhava et al found that lower back pain & neck pain as the most prevalent musculoskeletal impairments among bus drivers [12]. The study revealed that in between age range 18 to 35 years, most of age group was more than 32 years & considering the educational level more than half reported illiterate.…”
Section: Discussionmentioning
confidence: 99%